(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze the profile of live births in the State of Alagoas, belonging to northeastern Brazil, correlating with the number of prenatal consultations in the ten-year time frame, between 2009 and 2018. This is a descriptive, retrospective study with a quantitative approach, carried out through data from the Information System on Live Births (SINASC). The results showed that there was a positive relationship between the increase in the number of consultations over the years, with a predominance of a higher age group and higher education among women, demonstrating that this group has more chances of access to health services. Moreover, when comparing the best neonatal outcomes, it was demonstrated that women with a high prenatal coverage presented better results regarding the Apgar index in the 1st and 5th minute and better birth weight. Based on this, although an increase in the number of consultations over the years, with better neonatal outcomes, has been evidenced, this factor does not guarantee efficacy and quality of care when analyzed alone. It is necessary that managers and health professionals take responsibility for caring for women in the pregnancy cycle, for an effective implementation of public policy on women’s health.